A latitudinal signal in the relationship between species geographic range size and climatic niche area. Issue 12 (19th October 2022) - Dallas, Tad A.; Kramer, Andrew
Abstract : Species with broader niches may have the opportunity to occupy larger geographic areas, assuming no limitations on dispersal and a relatively homogeneous environmental space. Here, we use data on a large set of mammal (n = 1225), bird (n = 1829) and tree (n = 341) species to examine the 1) relationship between geographic range size and climatic niche area, 2) influence of species traits on species departures from this relationship and 3) sensitivity of these relationships to how species range size and climatic niche area are estimated. We find positive geographic range size–climatic niche area relationships for all taxa, with residual variation dependent on latitude, and differing from a null model for mammals and birds, but not for trees. Together, we provide support for this general macroecological relationship which is dependent on space, weakly influenced by species traits, and different enough from a null model to suggest that geographic and demographic processes are important.